2021
DOI: 10.3390/s22010060
|View full text |Cite
|
Sign up to set email alerts
|

Wristbands in Home-Based Rehabilitation—Validation of Heart Rate Measurement

Abstract: The possibility of using a smartwatch as a rehabilitation tool to monitor patients’ heart rates during exercise has gained the attention of many researchers. This study aimed to evaluate the accuracy and precision of the HR measurement performed by two wrist monitors: the Fitbit Charge 4 and the Xiaomi Mi Band 5. Thirty-one healthy volunteers were asked to perform a stress test on a treadmill. Their heart rates were recorded simultaneously by the wristbands and an electrocardiogram (ECG) at 1 min intervals. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Many studies reported that the accuracy of PPG-based smartwatches for HR measurement during physical activity is generally lower than that during rest [ 10 , 12 , 15 , 18 ]. For example, a recent study published in 2022 by Alfonso et al involving PPG-based, wearable devices reported that this technology demonstrated good-to-excellent agreement in measuring HR during rest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies reported that the accuracy of PPG-based smartwatches for HR measurement during physical activity is generally lower than that during rest [ 10 , 12 , 15 , 18 ]. For example, a recent study published in 2022 by Alfonso et al involving PPG-based, wearable devices reported that this technology demonstrated good-to-excellent agreement in measuring HR during rest.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, MAPE expressed the percentage difference of the HR acquired by the smartwatch relative to that of the CEM, and a value < 10% was considered reliable accuracy [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Devices from popular brands, including Apple (Apple Inc, Cupertino, California, USA), Fitbit (Fitbit Inc, San Francisco, California, USA), Samsung (Samsung Electronics Co., Ltd., Suwon, South Korea), Garmin (Garmin Ltd, Olathe, Kansas, USA), and Polar (Polar Electro, Inc., Kempele, Finland) demonstrate high agreement for HR measurements during sleep and/or rest when compared with criterion measures (i.e. ECG or chest HR monitor) [29–35]; however, as exercise intensity increases, measurement error is more likely to occur [29–32,36,37 ▪ ,39]. The extent of this relationship can be influenced by activity type, arm movement, and device [32,40].…”
Section: Accuracy Of Wrist-worn Commercial Devices For Assessing Phys...mentioning
confidence: 99%
“…However, wearable technology faces several important limitations, some biologically inherent and others technological, that avert the proliferation of wearable medical devices, including the lack of high-quality validation studies at different intensity levels [3,13,15,19,42,43,[54][55][56][57][58][59][60][61]. Although accuracy in HR measurement is acceptable in chest strap and electrode-based heart rate monitors, the accuracy of HR measurement in wrist wearables with PPG is uncertain [56,[62][63][64][65][66]. The accuracy of any wearable medical device is increasingly relevant, as it can influence both medical decisions and patient outcomes [15,19,42,43,60].…”
Section: Introductionmentioning
confidence: 99%